2021
DOI: 10.1002/ccr3.5078
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis and neonatal sepsis due to extended‐spectrum beta‐lactamase‐producing Escherichia coli infection: a case report

Abstract: Chorioamnionitis is an acute inflammation of the membranes and chorion of the placenta typically due to ascending polymicrobial infection in the setting of membrane rupture. It is a common complication of pregnancy associated with significant maternal, perinatal, and long‐term adverse outcomes. We present a case of placental infection leading to preterm delivery, severe neonatal sepsis, maternal wound infection, postnatal readmission, and prolonged hospital stay. This virulent infection was caused by multidrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…In a study by Shittu et al, poor maternal morbidity was noted in women with MDRO CA leading to maternal septicemia and wound infection. In their study, the patient had readmission with the same MDRO-induced surgical site infection which caused CA [ 5 ].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…In a study by Shittu et al, poor maternal morbidity was noted in women with MDRO CA leading to maternal septicemia and wound infection. In their study, the patient had readmission with the same MDRO-induced surgical site infection which caused CA [ 5 ].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…On the other hand, the absence of a cycling pattern and maternal tachycardia were associated with poor neonatal outcome [ 22 ]. In another case report, recurrent variable decelerations were noted with baseline tachycardia and poor variability with MDRO-induced CA [ 5 ]. Sukumaran et al reported an increase in baseline fetal heart rate and variable decelerations in women with CA [ 23 ].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
See 3 more Smart Citations